Uso de métodos analíticos en el diseño estructural de una edificación de acero de uso mixto en situación de incendio (2019)
In the structural design of a building in a fire condition, two methodologies can be used: prescriptive and analytical. Because the prescriptive design is too expensive and unreliable for the passive protection of steel structures, this paper presents an analytical and rational methodology, based on the risk of fire occurrence, according to the methods proposed in the Eurocode and in American regulations for dissemination purposes and in order to facilitate its understanding and implementation in structural design